Pete at the beach - Dean, James, 1957- (New York : Harper, an imprint of HarperCollins Publishers, 2013)
"Pete is spending the day at the seashore. He has fun collecting shells and building a sand castle. But the beach is very hot. There is a whole ocean for Pete to cool off in, but it looks scary. Pete's brother, Bob, offers to teach Pete to surf. Will that be enough to help Pete get over his fear of the water?"--Description from Amazon.com.
"My first shared reading."
Keywords: Cats -- Juvenile fiction; Beaches -- Juvenile fiction; Cats -- Fiction; Beaches -- Fiction